Streptococcus anginosus Pyogenic Liver Abscess following a Screening Colonoscopy - Francis Bonenfant; Étienne Rousseau; Paul Farand (Canadian Journal of Infectious Diseases and Medical Microbiology)
A previously healthy 58-year-old man presented with a septic thrombosis of the right hepatic vein and a pyogenic liver abscess (PLA) one week after undergoing a screening colonoscopy. Blood cultures and a radiological drainage specimen were both positive for Streptococcus anginosus. Evolution was favourable after six weeks of antibiotherapy. To the authors’ knowledge, the present report is the first to describe a PLA following a screening colonoscopy with no intervention. The authors hypothesize that silent microperforations during colonoscopy contributed to the infection. Although 20% to 40% of reported PLA cases are cryptogenic in the literature, it may be because of failure to recognize and report a precipitating factor such as colonoscopy. As more cases similar to the present case are reported, the number of cryptogenic cases may decrease.